The Effect of Social Capital on Governance and Sustainable Livelihood of Coastal City Community Medan. (25th November 2015) - Maas, Linda Trimurni; Sirojuzilam,; Erlina,; Badaruddin,
Abstract: Sustainable Livelihoods is a way of thinking that focuses on human development to recover and increase the ability and capital owned in the present and future. The aim of this research is analysing the relationship between social capitals to improve the ability in the use of governance on sustainable livelihoods. The population is coastal communities of Medan. Samples are 300 respondents were taken by accidental sampling technique. Data were collected by questionnaire; data analysis method is Structural Equation Modelling (SEM). The results are social capital significantly affects governance in Coastal Areas of Medan but governance does not significantly affect the sustainable livelihoods Coastal communities. And social capitals significantly influence sustainable livelihoods.